Ecosystems Services Provided by Bats Are at Risk in Brazil - Brasileiro, Lais A. M.; Machado, Ricardo B.; Aguiar, Ludmilla M. S. (Frontiers in Ecology and Evolution, 2022)
Ecosystem services (ES) are essential for human society worldwide. Freshwater supply, nutrient cycling, food production, pest control, spiritual and cultural aspects are examples of ecological processes commonly occurring in well-preserved regions that benefit us. Bats play an essential role in providing such services, primarily insect suppression, plant pollination, and seed dispersal. Human activities have affected Earth's systems, compromising species and ecosystems and, consequently, the ES provision. Brazil is a country with many bat species but is also one of the world's leaders in deforestation. Here we aimed to identify important regions for ecosystem services provided by bats, assuming that the presence of the species represents the provision of the services. First, we used a Maximum Entropy algorithm to model the distribution of 125 bat species, which correspond to 69.1% of the Brazilian species. We classify all species into 10 different guilds, which resulted from a combination of three body sizes and four predominant food specializations (frugivores, insectivores, nectarivores, and carnivores). The guilds were associated with seed dispersion, pest control, pollination, and animal control (e.g., rodents). Then, we created a 0.5x0.5-degree grid to represent an index of ES per guild, which is the sum of the product of the bat's size (1, 2, or 3) by the area occupied of each species in each cell. For comparison, the index was scaled from 0 to 1. Finally, we used a map of current land use to compare the effects of deforestation on the provision of ES in each cell. Our results indicate a substantial reduction in the provision of ES by bats in extensive parts of the central and eastern parts of Brazil. We suggest that degraded area restoration should be promoted in areas with high ES values and areas near cities and croplands and that a precautionary approach of promoting the conservation of high provider richness should be applied to protect the continuation of bat’s ES.